@Animalcatcher.ac: Cultural Zoology on the Instagram Platform - Gabriel de Sousa Silva, Rhayan; Gonçalves da Costa, Karla (Guará Journal, 2025)
Cultural zoology works by exposing the science behind zoology's influence on diverse cultural universes. Parallel to this, Instagram establishes a virtual community with numerous profile types. Combining these proposals, this study aimed to explore the accessibility of the Instagram platform, aiming to continue the scientific outreach and cultural zoology activities developed by the page @animalcatcher.ac. To this end, content was produced over the course of a year and the page's growth and performance recorded. During the study, there was an increase of 16 new animals cataloged in the digital database, which currently has 75 species. The most prominent posts were related to Spider-Man, with the highest number of likes and reach, and another relating dogs to physics, with the highest number of impressions. Follower growth was continuous, and, monthly, posts had an average reach of 86% and an average of 4,858 impressions. The majority of the audience was young people aged 18 to 24, with a small discrepancy between men and women. Despite some challenges, the results presented show that scientific dissemination, addressing cultural zoology, through social media, proved to be possible and relevant.
Keywords: Pop-culture; Cultural zoology; Social network; Pokémon; Teaching